Penerapan Konsep Arsitektur Tropis Pada Bangunan SMP dan SMA Swasta di Sindang Barang Bogor - Muhammad Abdul Qodir; Harfa Iskandaria; Karya Subagya (MAESTRO, 2020)
ABSTRACT Every year there are many children, especially in junior and senior high schools who are refused entry to public schools. As in Bogor Regency, there are many junior high and high school aged children who are refused entry to public schools due to limited school capacity. Private Junior High School (SMP) and Senior High School (SMA) buildings with the concept of tropical architecture can be an alternative to State Schools that fulfill junior and senior high school education facilities and can overcome tropical climate problems in Bogor Regency. Tropical architecture adapts the shape of the building to the influence of tropical climates that have certain characters. This will give a characteristic of a private school building that is able to provide thermal comfort to private school building users. As well as the use of local materials that are suitable for tropical climates can be a special attraction for private school buildings that apply the concept of tropical architecture.